HYPERNATREMIA IN CHILDREN AND NEUROLOGICAL DISORDERS, ITS MANAGEMENT (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Hypernatremia (HRN), defined as serum sodium >145 mmol/l, represents hyperosmolality. Although it reflects a deficiency of water relative to sodium, total body sodium may be high, normal or low. HRN is mirror image of hyponatremia. However, no large-scale studies have been conducted in the pediatric setting to inform this recommendation. Therefore, this study aimed to report the association between the rate of correction of hypernatremia, neurological outcomes, and all-cause mortality in children.